MAKNA KATA TAQWA DALAM AL-QURAN : SURAT AL BAQARAH : MAKNA KATA TAQWA DALAM AL-QURAN : SURAT AL BAQARAH - Nafidul Ihsan (Pascasarjana Institut Agama Islam Al-Qolam, 2022)
In the context of Islam, having taqwa or the qualities of truth is a must because taqwa reflects the level of faith of a Muslim. Therefore, the purpose of this study is to identify the characteristics of taqwa in Surah Al-Baqarah. The data of this study were obtained from the verses in Surah Al-Baqarah which include the word taqwa in it, interpreting the verses that contain the characteristics of Taqwa by using an established interpretation in the field of the Qur'an as a guide in marking the characteristics of taqwa. in sampling these verses. Two experts in the field of Qur'anic exegesis validate the attributes of Taqwa extracted from each selected verse. The results of the study revealed several categories of Taqwa traits, namely monotheism, doing good to others, praying, paying zakat, respecting rights, repentance, doing good deeds, correct communication, being grateful, sincere. Among the attributes of the Taqwa category, the main emphasis is on monotheism or belief in the oneness of Allah. This finding helps in increasing the understanding of the attributes of Taqwa, which is very useful for non-academic Muslims in strengthening their Islamic faith according to what is commanded in the Qur'an. Keywords: Taqwa, Al-Qur’an, Qs. Al-Baqarah